Presentasi Diri Etnik Cina Bangka dalam Hubungan Bisnis dengan Etnik Melayu Bangka - Agustina Zubair (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2013)
This article is based on research into intercultural communication competence Bangka ethnic Chinese business relations with ethnic Malay Bangka. Interesting phenomenon of the existence of ethnic Chinese Bangka and business activity is related to the reaction shown by an ethnic Chinese as willing as this ethnic group dominant culture that is ethnic Malay Bangka like learning a language, dress etiquette, talking, hanging out with the group leaning Malay culture, thereby minimizing differences in cultural backgrounds brought by minority individuals. What was achieved ethnic Chinese and Malays Bangka Bangka be seen as something that is formed from the learning process, from the longexperience, delivered and learned through interaction in the family and the environment.